Report in practice in industry training in fish processing technology. - Esporlas, Amelia E. (College of Fisheries, University of the Philippines, 1978)
Practice-in-industry training in fish preservation opens a broader know-how in fish processing and handling which are introduced in theories, the application of which are limited to simple experiments in the laboratory. Evaluations made on these experiments are applied by the student in making recommendations of food quality, processing and handling, etc., to the industry she/he is working with. The industry then, while paying more for a good quality product upgrades some methods of handling which are in a way interrelated with proper handling at sea, at transport and during processing. This report covers training ion the pilot plant's refrigeration and cold storage at food terminal incorporated (FTI) Taguig, Metro Manila and at fish processing establishments in Mercedes, Caamarines Norte which are engaged in salting, drying, smoking, and bagoong making. Fish processors from these establishments were interviwed and asked about problems in industry, which the student is able to evaluate. Many other information were taken like location of the plant, main products processed, processing techniques, number of workers in the plant, materials used, sanitation and marketing.